COLOR REMOVAL FROM PEAT WATER USING PHOTOCATALYTIC (UV-TiO2) - AWFA (NIM: 25314713), DION
Sumatera Island is one of the islands in Indonesia that has a big potential of peat land. This will affects the characteristics of the water in this area. Generally, peat water will has high color intensity, low pH, and high organic content. It was mainly caused by humic acid as a main substance in peat water. Now on, generally we still use coagulation-floculation and followed by filtration to treat this kind of water. But these technologies still not enough to remove the color significantly. That’s why we need advanced technologies such as photocatalytic using TiO2. Using TiO2 powder as a catalyst sometimes will give another problem such as post separation problem; one of the solutions is using impregnation method. Clay as an immobilizer for TiO2 has a big potential usage because thissystem has several advantages; one of it is increasing specific surface area from catalyst. Preliminary treatment using coagulation has achieved highest turbidity and color removal efficiency at pH 6.5 and aluminum sulphate dosage 70 mg/L. The efficiencies for turbidity and color were 87.691% and 83.578%. The remaining color will be treated by photocatalytic process. The best color removal efficiency by impregnation clay is 7.992%-14.146% and 7.335%-13.505% for TiO2. Photocatalytic process will achieve the best result while in pH 4.8 (acid) and catalysts dosage 0.25 g/L with Langmuir Hinshelwood kinetics for TiO2 is 0.0181/minute and 0.0206/minute for impregnation clay. Color removal mechanism in photocatalytic process is based on oxidation process of carboxyl group and aromatic ring by radical OH*. That’s why, photocatalytic process especially using impregnation clay has a potential to remove color in peat water.